THEORETICAL AND METHODOLOGICAL FUNDAMENTALS OF PRODUCT RANGE MANAGEMENT - DYKHA, Mariia; MAKSYMCHUK, Vasyl; VILCHYNSKA, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article substantiates the importance of managing the range of products in the general management system. It is noted that the assortment policy of a business entity depends on its mission, the developed strategy and tactics, and on the other hand, the assortment policy affects the formation of strategy and determines the tactical decisions of business entities. It is justified that the formation and implementation of the assortment policy of business entities requires a clear idea of the strategic goals of economic activity; clear understanding of one’s own capabilities, analysis of the external environment, industry and market trends. It is justified that in the product assortment management system it is advisable to follow the algorithm / procedure for evaluating and improving the assortment structure, which clearly structures the work on the performance of tasks, removes the need to spend time and resources on periodic assignment of tasks to specialists of structural units, etc. The algorithm provides certainty regarding: 1) the frequency of evaluation of the range of products by the business entity; 2) methods on the basis of which the existing assortment structure of production and feasibility of production of potentially new types of products that can be introduced into production will be evaluated; 3) responsible persons (specialists of the structural unit/department) for performing assortment evaluation procedures and preparing conclusions/working out draft decisions regarding the assortment. A model of formation/adjustment of the assortment portfolio of business entities is proposed. Making managerial decisions according to the model should be based on the results of assessing the impact of external environmental factors, the existing assortment structure, the feasibility of introducing new types of products, and the results of assessing the potential / opportunities for expanding production, forecasting and planning, etc.